2019
DOI: 10.1088/1361-6463/ab1c99
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of magnetic properties by alternating the order of hard/soft bilayers with various thicknesses

Abstract: Controlled tuning of magnetic anisotropy and damping is essential in ferromagnetic systems for various spintronic applications. In this context, magnetic bilayers with different thicknesses of soft (Co) and hard (Co40Fe40B20) layers have been prepared using magnetron sputtering technique by alternating the order of the constituent magnetic layers. We have observed an increase in the coercive field (HC) by increasing the thickness of the Co layer. Further, for the same constituent layers, HC increases for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
(35 reference statements)
2
6
0
Order By: Relevance
“…Angle dependence of magnetic hysteresis loops and domain images captured at coercive field for sample M0 are shown in Figure . The coercivity of CoFeB film is found to be ∼2.5 mT which is comparable to literature values . Domain images show similar patch like domains at all angles of measurement.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Angle dependence of magnetic hysteresis loops and domain images captured at coercive field for sample M0 are shown in Figure . The coercivity of CoFeB film is found to be ∼2.5 mT which is comparable to literature values . Domain images show similar patch like domains at all angles of measurement.…”
Section: Resultssupporting
confidence: 85%
“…The coercivity of CoFeB film is found to be ∼2.5 mT which is comparable to literature values. 21 Domain images show similar patch like domains at all angles of measurement. Hysteresis loops as well as the domain structures are independent of angles at which it was measured.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…The CoFeB target is at an angle of 30° with respect to the substrate normal due to the in-built geometry of the deposition system. Such an oblique-angle deposition-induced uniaxial anisotropy has been reported earlier. , It should be noticed that there is a change in the coercive field ( H C ) in the bilayer samples as compared to the single-layer reference sample. The values of H C are 1.23, 0.71, 0.91, and 0.81 mT for samples S1, S2, S4, and S5, respectively.…”
Section: Resultssupporting
confidence: 78%
“…Also, little deviation in the H res value from all other samples is observed in sample S4 and this may be due to modified exchange coupling at the interface of the ferromagnetic layers. We reported earlier that direct exchange coupling between magnetic layer leads to the enhancemet of the Gilbert damping constant α value 30 . We are getting simultaneously high coercivity and less α values in sample S3 which is good for FMR applications.…”
Section: Fmr Analysismentioning
confidence: 91%
“…We reported earlier that direct exchange coupling between magnetic layer leads to the enhancement of the Gilbert damping constant a value. 30 We are getting simultaneously high coercivity and less a values in sample S3 which is good for FMR applications. Omelchenko et al, reported the tuning of damping by alternating the order of Py/Fe bilayers deposited on Si substrate with Ta as seed layer.…”
Section: Fmr Analysismentioning
confidence: 95%